For other ways of life: cosmopolitics in regulations, utopias and spiritualities - Cunha, Pedro Henrique Azalim; Monte-Mór, Roberto Luís de Melo (Revista Nacional de Gerenciamento de Cidades, 2023)
This article critically approaches our anthropocentric relationship with the planet and raises alternatives to think about cosmopolitical regulations and utopias as potentialities for the reestablishment of the planet’s equilibrium. To do so, it is necessary to understand the Earth as a living organism, Gaia, as in fact various peoples and cultures already recognize it. We try to imagine how other worlds, other ways of living and relating to other beings and natural elements would be possible. We thus aim to think about, question, and eventually regulate the rights of nature and its relations with health and spirituality in the appropriation and production of social space, of living spaces. In spite of the advances observed in Latin America in the regulation of society/nature relations, Brazil is still characterized by an anthropocentric legislation that references human domination over other beings and elements. The apparent advances in the line of ecological modernization, or ’green stamps’, in fact do not address the issues and causes that determine or contribute to the destruction of the planet, or even to the threats posed today to all organisms, including Gaia herself. Cosmopolitical regulations and utopias can be empowered to achieve other ways of life, changing the hegemonic anthropocentric perspective to an ecocentric approach, and perhaps even changing the dominant materialist paradigm to a new paradigm that recognizes the spiritual-materialist dialectical relationship and the necessary sacralization of everyday life.